Multi-omics characterization of the osmotic stress resistance and protease activities of the halophilic bacterium: Pseudoalteromonas phenolica in response to salt stress - Song, Won Suk; Kim, Seong Min; Jo, Sung Hyun; Lee, Jae Seung; Jeon, Hyo Jin; Ko, Byoung Joon; Choi, Kwon Young; Yang, Yung Hun; Kim, Yun Gon (RSC Advances, 2020)
The halophilic bacterium Pseudoalteromonas phenolica is well known as a promising candidate that enables the recycling of organic wastes at high salinity. However, for industrial applications of P. phenolica further research is required to explore the biological mechanism for maximizing the activities and productivities of this bacterium. In this study, we investigated the osmotic stress resistance and specific protease activities of P. phenolica in a normal-salt medium (0.3 M NaCl) and high-salt medium (1 M NaCl) based on intra- and extracellular multi-omics approaches. Proteins related to betaine and proline biosynthesis were increased under high salt stress. The targeted metabolite analysis found that proline was overproduced and accumulated outside the cell at high salinity, and betaine was accumulated in the cell by activation of biosynthesis as well as uptake. In addition, extracellular serine proteases were shown to be upregulated in response to salt stress by the extracellular proteomic analysis. The specific proteolytic activity assay indicated that the activities of serine proteases, useful enzymes for the recycling of organic wastes, were increased remarkably under high salt stress. Our results suggest that betaine and proline are key osmoprotectant metabolites of P. phenolica, and they can be used for the improvement of protease production and P. phenolica activities for the recycling of high-salt organic wastes in the future. This journal is
Keywords: Biological mechanisms; Halophilic bacteria; Metabolite analysis; Protease activities; Protease production; Proteolytic activities; Proteomic analysis; Pseudoalteromonas